(untitled) (Bangladesh Journal of Physics, 2020)
In this work, molecular dynamics (MD) study of triglyme (G3) solution containing lithium bis (trifluoro methyl sulfonyl) amide (Li[TFSA]) were investigated using classical atomistic force fields. G3 is a typical solvent used in non-aqueous Li-air battery. It shows here coordination of Li+ with G3 and [TFSA]- does not significantly change with increasing the concentration of G3 but self-diffusion coefficient of all the ions increases with increasing G3 concentration. The density of [Li(G3)[TFSA] complex decreases with increasing G3 concentration which lead to accelerate diffusivity of ions. Bangladesh Journal of Physics, 27(1), 13-22, June 2020